The Influence of Transformational Leadership and Organizational Culture on Employee Performance at Bhayangkara Hospital Surakarta in 2026 - Catur Joko Widodo (Indonesian Journal of Innovation Science and Knowledge, 2026)
Employee performance is a key determinant of hospital service quality. Transformational leadership and organizational culture are organizational factors that may influence employee performance. This study analyzed the relationship and simultaneous contribution of transformational leadership and organizational culture to employee performance at Bhayangkara Hospital Surakarta. A quantitative analytical study with a cross-sectional explanatory design was conducted from January to April 2026. The population consisted of 120 employees, with 90 respondents selected using proportionate stratified random sampling. Data were collected using questionnaires, observation instruments, and secondary hospital data. Statistical analyses included descriptive statistics, Spearman Rank correlation, and ordinal logistic regression (PLUM). Most respondents rated transformational leadership (82.2%), organizational culture (82.2%), and employee performance (84.4%) as good. Transformational leadership was positively associated with employee performance (r=0.362; p<0.001), whereas organizational culture showed a positive but non-significant relationship (r=0.201; p=0.057). The ordinal regression model was significant (χ²=14.607; p=0.001) and explained 24.6% of the variance in employee performance (Nagelkerke R²=0.246). Strengthening transformational leadership and organizational culture simultaneously may improve employee performance through leadership development, organizational value internalization, and continuous performance evaluation.